ANALISIS PERSPEKTIF CALON GURU PADA APLIKASI “RUMAH BELAJAR” - Wisnu Busky Wardhana; Christine Wulandari Suryaningrum; Rohmad Wahid Romdhani (SIGMA, 2022)
The background. of this research is due. to the impact caused by Covid-19. urge educators to carry out learning. distance that is almost unheard of. and the obstacles experienced by parents due to the pandemic. covid-19 is a tough economy. The learning house portal is an alternative for parents in helping their children to learn independently. at home at this time and the free use of the learning house can help parents, teachers and students. So the need for a prospective teacher perspective where one day will become a teacher in a school is an important point where opinions. from prospective teachers can be a point of view. for a change in the future. The results obtained that prospective teachers assess that the home study application can assist teachers in delivering learning materials during the. current Covid-19 period because in the learning house the material presented is clear, always follows the current learning developments, there are many features that can help and improve student learning. Not only in the form of electronic books, there are also videos and questions that students can practice immediately after studying the material. The conclusion. of the study is that. the perspective of prospective teachers argues that utilizing this application is a new way to increase student. learning motivation which by using this application makes it. easier for students. to find materials that they do not understand.